KONSENTRASI HAMBAT MINIMUM EKSTRAK ETHANOL DAUN BELUNTAS (Pluchea indicha) DAN DAUN KEMANGI (Ocimum sanctum L) SERTA CAMPURAN DAUN BELUNTAS DAN DAUN KEMANGI TERHADAP PERTUMBUHAN BAKTERI (Escherichia coli, Staphylococcus aureus) PADA PENDERITA PROSTATITIS - Isnainy Hidayati; Sukarjati Sukarjati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
Prostatitis is a disease caused by bacteria, especially (E. coli, S. aureus). Treatment of diseases using antibiotics cause negative effects on the environment, pathogenic bacterial resistance, and antibiotic residues. Therefore, it is necessary to develop an antibacterial alternative from natural ingredients for the treatment of this disease. One of the natural ingredients that are antibacterial is basil leaf extract and beluntas leaves that have antibacterial inhibitory power. This research aims to prove the antibacterial activity of basil leaf extract and beluntas leaves in vitro. The treatments used were P0 (control), P1 (1.56%), P2 (3.125%), P3 (6.25%), P4 (12.5%), P5 (25%), P6 (50% ), P7 (100% ).. The parameters observed were bacterial growth on culture medium. The result of MIC (the lowest concentration of dilution that can inhibit bacterial growth) is seen from the treatment media turbidity and MBC result (the lowest concentration of dilution that can kill bacteria) seen from bacterial colony growth on NAP media. Data were analyzed descriptively. The results showed that basil leaf extract and beluntas leaves can inhibit growth or killing (E. coli, S. aureus) in prostatitis patients. Keywords: Prostatitis, antibacterial activity, microbial inhibition